Misionella (Iridaceae: Tigridieae) a new genus from Campos eco-region of Southeast South American grasslands - Deble, Leonardo Paz (Balduinia, 2025)
It is proposed the new genus Misionella belonging to the tribe Tigridieae. Misionella is closely related to the genera Cypella, Kelissa and Onira, and vegetative and anatomically also resembles Herbertia. Misionella is constituted by two species, Misionella Hauthalii and Misionella opalina (with two subspecies: opalina and minuticristata). Misionella is endemic on grassland areas occurring in northeast Argentina (Corrientes and Misiones provinces), center and northwestern Rio Grande do Sul state, Brazil and southern Paraguay (Itapuã and Paraguari departments ). The genus Misionella is taxonomically revised, and its species are described and illustrated in detail and its geographic distribution is represented on a map. Data on etymology, geographic distribution, habitat, phenology, conservation, uses and vernacular names are provided, as well as discussions of taxonomic relationships of Misionella with related taxa. A dichotomous key for distinguishing the genera of Iridaceae-Tigridieae from South America is presented.